Public participation in marine spatial planning in Iceland - Wilke, Maria (Frontiers in Marine Science, 2023)
Introduction Marine Spatial Planning (MSP) aims at ecosystem-based management of ocean resources that brings different stakeholders and the public together to discuss their conflicts of interest and forge a sustainable path forward. Public participation is a crucial element of MSP to make it democratically legitimate and sustainable in the long-term. MSP was formally introduced by law in Iceland in 2018 and two projects were initiated in the Westfjords and Eastfjords in 2019, with one further planned in Skjálfandi Bay. Methods To assess the scope and depth of public participation in those MSP projects, data was collected through semi-structured interviews (n=80), conversations, observations and document analysis during the data gathering and proposal stages of the planning processes. Results The results show that a limited group of people including institutional actors and formal stakeholders had been engaged in the information gathering stages of the process, but in the later phases of decision-making, local community members were notably absent. Discussion/Conclusion This lack of public participation highlights the need for more in-depth communication about the MSP process and marine issues in the adjacent communities as well as an urgent need for inclusion of the public into marine decision-making and MSP.